Long-Term Outcomes in Crosslinking Therapy for Patients with Progressive Keratoconus - Tevfik Serhat Bahar; Vedat Şahin; Yusuf Ayaz; Mustafa Ünal (Diagnostics)
Background/Objectives: To investigate the mid- and long-term postoperative follow-up results of corneal crosslinking (CXL) treatment (using epi-on and epi-off techniques) in progressive keratoconus. Methods: This was a retrospective single center study conducted between October 2013 and July 2020. Patients who received CXL treatment with a diagnosis of progressive keratoconus were included in the study. Preoperative and postoperative recorded examination findings of autorefractometry, visual acuity, endothelial cell counts by specular microscopy, and corneal topography were analyzed retrospectively. According to the latest measurements, the results were divided into two groups: measurements between 6 and 12 months and measurements between 1 and3 years. Results: A total of 290 operated eyes of 201 patients were included in the study. The mean age of the patients was 21.34 ± 5.77 years, and 119 (59.2%) were male. Epi-off CXL was performed on 269 (92.8%) eyes and epi-on procedure was performed on 21 (7.2%) eyes. CXL had no significant effect on visual acuity. Significant improvement was observed in topographic/keratometric features of the cornea both after 6–12 months and after 1–3 years. Significant decreases were observed in K1 (p < 0.001), K2 (p < 0.001), KM (p < 0.001) values compared to the initial level. Conclusions: CXL treatment is an important treatment method in the treatment of keratoconus, preserving visual functions, significantly reducing the severity of astigmatism, and stopping the progression of keratoconus. Additionally, although epi-off and epi-on CXL methods were compared in our study, the sample size was limited, and more comprehensive and long-term studies are needed.